Jonathan F. Krell. Ecocritics and Ecoskeptics: A Humanist Reading of Recent French Ecofiction. Liverpool UP, 2020. - Lisa Connell (Studies in 20th & 21st Century Literature, 2022)
Review of Jonathan F. Krell. Ecocritics and Ecoskeptics: A Humanist Reading of Recent French Ecofiction. Liverpool UP, 2020, 261 pp.
Keywords: ecocriticism; humanism; French Ecofiction